The Use of Artificial Neural Network to Optimize The pH Response Range of Chlorophenol Red - F. Wong; M. Ahmad; L. Y. Heng (ASEAN Journal on Science and Technology for Development, 2003)
Artificial Neural Network (ANN) had been used in this study to extend the response range of the pH indicator.  The input from absorbance values of the absorbance spectra of chlorophenol red at different pH was used to train the ANN.  During the training process, the coefficient values of the ANN will be adjusted to obtain the desire output.  In this research, back propagation algorithm had been used for optimizing the response range of the pH indicator chlorophenol red in solution.  The result indicates that the use of ANN enable the pH response range to be extended from 4.8-6.8 to 1.0-10.0.